2018
DOI: 10.1182/blood-2018-99-111061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy and Toxicity of CD19-Specific Chimeric Antigen Receptor T-Cells Alone or in Combination with Ibrutinib for Relapsed and/or Refractory CLL

Abstract: Background We reported durable responses to CD19-specific chimeric antigen receptor-modified T-cell therapy (JCAR014) in relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL) patients (pts) after prior failure of ibrutinib (Turtle, JCO 2017; NCT01865617). In those pts, ibrutinib was not administered during CAR-T cell immunotherapy. Continuation of ibrutinib through leukapheresis, lymphodepletion and CAR-T cell therapy may prevent tumor progression after ibrutinib withdrawal, mobilize tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…Similar results were reported for patients who had been treated with ibrutinib from at least 2 weeks prior to leukapheresis until 3 months after CAR T cell infusion (n = 19), with an ORR of 88% . This compared to an ORR of 65% in similar patients treated in the absence of concurrent ibrutinib .…”
Section: Targeting Cd19 In Cllsupporting
confidence: 81%
“…Similar results were reported for patients who had been treated with ibrutinib from at least 2 weeks prior to leukapheresis until 3 months after CAR T cell infusion (n = 19), with an ORR of 88% . This compared to an ORR of 65% in similar patients treated in the absence of concurrent ibrutinib .…”
Section: Targeting Cd19 In Cllsupporting
confidence: 81%
“…Combining functional studies, immunophenotypic and new technologies, such as next generation sequencing to study the TCR repertoire, or single cell RNA sequencing, will complete insights into changes in T-cell immunity mediated by BTKis. Preliminary data from combination trials of ibrutinib and T-cell-directed immunotherapy, such as CD19 CAR-T cell therapy in R/R patients, have been promising [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…When CAR-T cells were administered as consolidation therapy for patients who did not achieve a complete response after at least six months of ibrutinib, a higher rate of sustained responses (CR rate of 43%) were observed compared to previous studies with CAR-T cells in ibrutinib-naïve patients (CR rates of 21-29%) [70]. In a subsequent study of CAR-T cells, ibrutinib coadministration improved response and attenuated grade ≥ 3 cytokine release syndrome (CRS) compared to CAR-T cells alone [71]. A clinical study investigating the combination of CAR-T cells and ibrutinib in CLL, small lymphocytic leukemia (SLL) and DLBCL is ongoing (NCT03960840).…”
Section: Of 14mentioning
confidence: 92%
“…It was shown that ≥5 cycles of ibrutinib therapy improved the expansion of CD19‐directed CAR T cells (CTL019), in association with a decreased expression of the immunosuppressive molecule programmed cell death 1 (PD1) on T cells and of CD200 on B‐CLL cells . Two clinical studies recently showed that this effect can be translated into higher efficacy of CAR‐T cells when combined with ibrutinib, yielding high response rates and a trend toward deeper remissions compared to CAR‐T cell infusions alone …”
Section: Current Challenges and Uncertaintiesmentioning
confidence: 99%